Trophic status, phytoplankton diversity, and water quality at Kafr El-Shinawy drinking-water treatment plant, Damietta - Mohamed Deyab (IWA Publishing, 2021)
This work aims to study the seasonal fluctuation in physicochemical characteristics, trophic status, and some pollutants influencing phytoplankton diversity, and water quality at a compact Kafr El-Shinawy drinking-water treatment plant, Damietta – Egypt seasonally during 2018. Phytoplankton distribution was affected by the trophic status of water, level of pollutants, and physicochemical treatment processes of water. The predominance of phytoplankton species, especially Aphanizomenon flos aquae (Cyanophyta), Gomphosphaeria lacustris (Cyanophyta), Microcystis aeruginosa (Cyanophyta), Nostoc punctiforme (Cyanophyta), Oscillatoria limnetica (Cyanophyta), Pediastrum simplex (Chlorophyta), and Melosira granulata (Bacillariophyta) in treated water was much less than that in raw water. Trihalomethanes (THMs) levels in treated waters were higher than in raw water, while lower concentrations of heavy metals were recorded in treated water. Intracellular levels of microcystins were lower, whereas the extracellular levels were higher in treated water than raw water, and the former recorded the highest level in raw water during summer. Hence, the levels of dissolved microcystins and THMs in treated water were higher especially during summer, the season of luxurious growth of Microcystis species. Trophic state index (TSI) was relatively high in raw water compared with treated water due to high concentrations of nutrients (total-P, total-N, nitrite, nitrate, and ammonia) in raw water. HIGHLIGHTS Phytoplankton composition was affected by the trophic status level of water and physicochemical treatment processes of water.; Phytoplankton cells control the levels of heavy metals in water.; THMs in treated water increased greater than those in raw water by the effect of physicochemical treatment of water.; Cyanobacteria produced cyanotoxins in water.;